Francisella tularensis Outer Membrane Vesicles Participate in the Early Phase of Interaction With Macrophages - Pavkova, Ivona; Klimentova, Jana; Bavlovic, Jan; Horcickova, Lenka; Kubelkova, Klara; Vlcak, Erik; Raabova, Helena; Filimonenko, Vlada; Ballek, Ondrej; Stulik, Jiri (Frontiers in Microbiology, 2021)
Francisella tularensis is known to release unusually shaped tubular outer membrane vesicles (OMV) containing a number of previously identified virulence factors and immunomodulatory proteins. In this study, we present that OMV isolated from F. tularensis subsp. holarctica strain FSC200 enter readily into primary bone marrow-derived macrophages (BMM) and seem to reside in structures resembling late endosomes in the later intervals. The isolated OMV enter BMM generally via macropinocytosis and clathrin-dependent endocytosis, with a minor role played by lipid raft-dependent endocytosis. OMV proved to be nontoxic and had no negative impact on the viability of BMM. Unlike the parent bacterium itself, the isolated OMV induced massive and dose-dependent proinflammatory response in BMM. Using transmission electron microscopy, we also evaluated OMV release from the bacterial surface during several stages of Francisella’s interaction with BMM. During adherence and the early phase of the bacterium’s uptake we observed numerous tubular OMV-like protrusions bulging from bacteria in close proximity to the macrophage plasma membrane. This suggests a possible role of OMV in the bacteria’s entry into the host cell. On the contrary, the OMV release from the bacterial surface during its cytosolic phase was negligible. We propose that OMV play some role in the extracellular phase of Francisella’s interaction with the host and that they are involved in the mechanism of the bacterium’s entry into macrophages.